Effects of regional certification on export activity, the case of the mexican leather-footwear cluster (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
La Marca Gto is a program created in Mexico in 2015 that looks for the creation of a good quality reputation of the products that receive it as a certification or regional trademark label. The objective of this research is to find an association between the participation of Mexicans MSMEs in this program and the beginning of export activity. A survey of 21 questions was applied to 69 SMEs that currently have this certification. The sample of this study is part of the Leather-Footwear Cluster of Guanajuato since this is one of the most traditional of the State that thorough the recent years has registered a decreasing volume of exports. The IBM SPSS Program was used to analyze the collected data and by applying McNemar test there was not found any association between the Marca Gto Certification and the beginning of export activity of the company.